Context-Specific Coordinately Regulatory Network Prioritize Breast Cancer Genetic Risk Factors - Wang, Shuyuan; Wang, Wencan; Wang, Weida; Xia, Peng; Yu, Lei; Lu, Ye; Chen, Xiaowen; Xu, Chaohan; Liu, Hui (Frontiers in Genetics, 2020)
Breast cancer (BC) is one of the most common tumors, leading the cause of cancer death in women. However, the pathogenesis of BC still remains unclear and the atlas of BC-associated risk factors is far from complete. In this study, we constructed a BC-specific coordinately regulatory network (CRN) to prioritize potential BC-associated protein-coding genes (PCGs) and non-coding RNAs (ncRNAs). We integrated 813 BC samples transcriptome data from TCGA and eight types of regulatory relationships to construct BC-specific CRN, including 387 transcription factors (TFs), 174 microRNAs (miRNAs), 407 long non-coding RNAs (lncRNAs) and 905 PCGs. After that, the Random Walk with Restart (RWR) method was performed on the CRN by using the known BC-associated factors as seeds, and potential BC-associated risk factors were prioritized. The leave-one-out cross-validation (LOOCV) was utilized on the BC-specific CRN, and achieved an area under the curve (AUC) of 0.92. The performances of common CRN, common protein-protein interaction (PPI) network and BC-specific PPI network were also evaluated, demonstrating that the context-specific CRN prioritize BC risk factors. Functional analysis for the top 100-ranked risk factors in the candidate list revealed that these factors were significantly enriched in cancer-related functions and had significant semantic similarity with BC-related Gene Ontology (GO) terms. Differential expression analysis and survival analysis proved the prioritized risk factors significantly associated with BC progression and prognosis. In total, we provided a computational method to predict reliable BC-associated risk factors, which would help improve the understanding of the pathology of BC and benefit the disease diagnosis and prognosis.